Molluscicidal effect of Euphorbia umbellata (Pax) Bruyns latex on Biomphalaria glabrata, Schistosoma mansoni host snail - Pereira, Luciana Patrícia Lima Alves (2017)
Euphorbia umbellata (Pax) Bruyns is an easily cultivated shrub, with occurrence in the tropical regions of the American and African continents. Chemical studies have revealed that the latex of this plant is rich in terpene compounds, which are highly toxic to snails Biomphalaria glabrata (Basommatophora: Planorbidae). The aim of this study was to evaluate the chemical composition and molluscicidal activity of the latex produced by E. umbellata, as well as the safety of its application in aquatic environments. The concentration of latex that killed 90% of the exposed snails after 24 h exposure (LC90) was 3.69 mg/L. Toxicity bioassays using Danio rerio (zebrafish) revealed that these animals were less susceptible to latex than planorbids. However, it is important to perform other toxicity tests to ensure the feasibility of using latex to control populations of mollusks that contribute to schistosomiasis transmission. A phytochemical screening performed with the E. umbellata latex identified the triterpenoid and coumarin class. Further studies are warranted to isolate, identify, and test the active compounds of E. umbellata latex in B. glabrata.